Proteomic Perspective of Cadmium Tolerance in Providencia rettgeri Strain KDM3 and Its In-situ Bioremediation Potential in Rice Ecosystem - Salaskar, Darshana A.; Padwal, Mahesh K.; Gupta, Alka; Basu, Bhakti; Kale, Sharad P. (Frontiers in Microbiology, 2022)
In this work, a multi-metal tolerant natural isolate Providencia rettgeri KDM3 from an industrial effluent, Mumbai, India, showed high cadmium (Cd) tolerance. Providencia rettgeri grew in presence of more than 100 ppm (880µM) Cd (LD50 = 100 ppm) and accumulated Cd intracellularly. Comparative proteome analyses following Cd exposure revealed molecular mechanisms underlying Cd tolerance. Among a total of 69 differentially expressed proteins in Cd exposed cells, de novo induction was observed for ahpCF operon proteins and L-Cysteine/ L-Cystine shuttle protein FliY, while Dps and superoxide dismutase proteins were overexpressed, indicating upregulation of a robust oxidative stress defense. A membrane transporter ENTRA1 showing homology to heavy metal transporter was also induced de novo. In addition, protein disaggregation chaperone ClpB, Trigger factor and protease HslU were also overexpressed. Forty six proteins belonging to major functional category of energy metabolism were found down-regulated. Further, addition of P. rettgeri to Cd-spiked soil resulted in significant reduction in the Cd contents [roots (11%), shoot (50%) and grains (46%)] of the rice plants. Cd bioaccumulation by P. rettgeri improved plant growth as well as grain yield. We conclude that the highly Cd-tolerant bacterium P. rettgeri is an ideal candidate for in-situ bioremediation of Cd-contaminated agricultural soils.